Pengaruh Kredit Yang Disalurkan Pada Profitabilitas Dengan Ukuran Perusahaan Sebagai Variabel Pemoderasi - Widi Artha, Made; Gst. Ayu Eka Damayanthi, I (E-Jurnal Akuntansi, 2019)
This study aims to obtain empirical evidence the effect of distributed credit on profitability, and the influence of company size on distributed credit to profitability relation. This research was conducted in the banking sub-sector companies listed on the Indonesia Stock Exchange from 2013 to 2017. The samples were determined using purposive sampling method, and the amount obtained was 120 observations. The data analysis technique used is Simple Linear Regression test and Moderated Regression Analysis (MRA). Based on the results of the analysis it was found that the distributed credit had a positive effect on profitability and the size of the company weakened the relation of distributed credit to profitability. The theoretical implications are to add insight and knowledge of the reader and additional reference to further research. The practical implications are as additional information for the bank companies in making decisions and investors before making an investment. Keywords:  Profitability, Distributed Credit, and Company Size